ChemInform Abstract: Physical Properties of Double Perovskite‐Type Barium Neodymium Osmate Ba2NdOsO6. Issue 8 (1st March 2013) - Wakeshima, Makoto; Hinatsu, Yukio; Ohoyama, Kenji
Abstract The title compound is synthesized from stoichiometric mixtures of BaO2, Os, and Nd2O3 (Pt crucible, Ag2O as oxygen donor in a second Pt crucible, 1270 K, 6 h).